Monitoring crustal movements in Istanbul using GNSS and GIS - Yucel, M. A.; Pirti, A.; Bayburt, S.; Bektas, O.; Buyuksarac, A. (IST NAZIONALE DI OCEANOGRAFIA E DI GEOFISICA, 2024)
Istanbul is located south of the Black Sea and north of the Marmara Sea. The seismic stresses and strains in Istanbul and the Marmara Sea are governed by the E -W and NE-SW tectonic characteristics. This research aims to establish the latest crustal motion parameters in Istanbul, utilising Global Navigation Satellite System (GNSS) surveys. A geodetic network was established for this study, comprising 1,159 temporary and nine permanent GNSS stations across Istanbul's Asian and European sectors. Between 2000 and 2020, GNSS measurements were taken, and horizontal and vertical crustal movements and velocity vector maps were produced using GNSS and Geographical Information System (GIS) tools. The GNSS data was processed using GIPSY-OASIS, Topcon Magnet Tools, and Leica Geo-Office software. The data was, then, analysed using ESRI ArcGIS software, which generated thematic maps of Istanbul using ordinary Kriging and trend surface analysis interpolation methods. The analysis results indicate a horizontal variation of the local velocity rate in the SW direction between 14.3 and 17.1 mm per year. Moreover, the data suggests that there is a subsidence variation between -0.7 and -2.0 mm per year. The study results show that the northern block of the North Anatolian Fault Zone moves horizontally towards the SW at an average rate of 16.3 mm per year. The study findings demonstrate a notable horizontal slip rate in the northern regions, whereas vertical subsidence is significantly observable in the eastern regions. The study involved the creation of Voronoi cells for each temporary GNSS station, followed by the calculation of regional shift magnitudes in the area surrounding each station. In regions with notable horizontal and vertical slippage, it would be beneficial to increase the number of observation stations, particularly within the extensive Voronoi cells. The longterm and continuous GNSS measurements greatly improve the study of ongoing crustal movement and tectonic deformation processes in north-western Anatolia.
Keywords: Istanbul; crustal movement; earthquake; GNSS; GIS; spatial interpolation; 1999 IZMIT EARTHQUAKE; MARMARA SEA REGION; FAULT ZONE TURKEY; NW TURKEY; GEODETIC CONSTRAINTS; STRAIN ACCUMULATION; GPS; SEISMICITY; DEFORMATION; VARIABILITY; Geochemistry & Geophysics